[Postpartum depression, neonatal hospitalization, and educational intervention]. [Article in Italian] • Depressione post partum, ospedalizzazione neonatale ed intervento educativo - Melania Picciau; Giovanni Ottonello; Susanna Floris; Massimiliano Zonza (Hygeia Press di Corridori Marinella, 2014)
Postpartum depression (PPD) is a non-psychotic depressive disease with varying severity, from moderate to severe, which originates after the 4th week from giving birth. At our hospital, a clinical approach to help mothers in a delicate period of their life was performed in 2 phases, in the first week of life during hospitalization of the newborn and after the 4th-6th week after delivery. The main instrument in use for the screening of PPD and used also in our study was the Edinburgh Postnatal Depression Scale (EPDS). Results are presented concerning in particular the correlations between EPDS and variables such as maternal characteristics and lenght of neonatal hospitalization.   Articoli Selezionati del Congresso "Medicina Narrativa e Comunicazione nella Pratica Clinica" · Cagliari · 14 Aprile 2014 Guest Editors: Massimiliano Zonza, Vassilios Fanos, Gian Paolo Donzelli